1999
DOI: 10.1007/s004150050530
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for levodopa-induced dyskinesias in Parkinson's disease

Abstract: To identify putative risk factors for levodopa-induced dyskinesias we studied the effect of several clinical variables on the occurrence of dyskinesias in a series of 168 consecutive patients with Parkinson's disease treated for at least 6 months with levodopa. Of these, 108 (64%) developed dyskinesias after a mean duration of levodopa treatment of 51.4 +/- 43.3 months. Patients tended to suffer dyskinesias on the side of the body first affected by Parkinson's disease. The overall probability of developing dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 17 publications
(16 reference statements)
6
96
0
4
Order By: Relevance
“…This study indicated that the acute symptomatic (motor stimulant) effect of A 2A antagonists may allow for chronic use of lower doses of L-DOPA, which are associated with a reduced risk of developing dyskinesia (Grandas et al, 1999;Fahn et al, 2004). , a relatively specific A 2A receptor antagonist, reduces parkinsonian symptoms without appreciably inducing or exacerbating L-DOPA-induced dyskinesia in nonhuman primates (Grondin et al, 1999;Kanda et al, 2000;Jenner, 2003Jenner, , 2005Kase et al, 2003;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 84%
“…This study indicated that the acute symptomatic (motor stimulant) effect of A 2A antagonists may allow for chronic use of lower doses of L-DOPA, which are associated with a reduced risk of developing dyskinesia (Grandas et al, 1999;Fahn et al, 2004). , a relatively specific A 2A receptor antagonist, reduces parkinsonian symptoms without appreciably inducing or exacerbating L-DOPA-induced dyskinesia in nonhuman primates (Grondin et al, 1999;Kanda et al, 2000;Jenner, 2003Jenner, , 2005Kase et al, 2003;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 84%
“…However, after several years of treatment, L-dopa-induced dyskinesia (LID) occurs in the majority of patients 1,[3][4][5] . These highly debilitating motor complications manifest as a variety of abnormal involuntary movements (AIMs), including severe and painful dystonic cramps (sustained abnormal muscle contractions), hyperkinetic and purposeless (choreiform) movements [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies looking for clinical risk factors in LIDs have shown that the occurrence of LIDs is linked with younger age at onset of PD, [31][32][33] as well as with longer disease duration. 32,34 The LIDs and non-LIDs groups of our PD cohort were clinically different (so that reached statistical significance) for sex, age, disease duration, the duration on dopaminergic medication, and LED Total .…”
mentioning
confidence: 99%